A Particle Based Ionomer Attachment Model for a Fuel Cell Catalyst Layer. Issue 1 (20th January 2020) - So, Magnus; Park, Kayoung; Tsuge, Yoshifumi; Inoue, Gen
Abstract : A particle model for ionomer attachment on carbon black in a Polymer Electrolyte Fuel Cell (PEFC) catalyst layer was developed based the random walk method. Two different methods of particle attachment were used that resemble different catalyst ink preparation conditions: the solution method and the colloidal method. In the solution method, the simulation of attachment is conducted on the aggregate structures and in the colloid method, the attachment is simulated on the agglomerate structures. The distribution of carbon black, ionomer and void space was used in a multiscale electrochemical simulator that calculated the mass/charge transfer and reaction in the catalyst layer. The results of effective oxygen diffusion coefficients are consistent with experimental result and show why the Bruggeman correlation often is a poor approximation for upscaling the effective diffusive and conductive components in PEFC porous media. The solution method allowed for a better proton conduction through the ionomer but resulted in a thicker ionomer film that increased the oxygen diffusive resistance. However, solution and colloidal method resulted in similar cell performances. Our model can aid in the design to develop fuel cell catalyst layers with improved performance.